1984
DOI: 10.1002/ar.1092100410
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis of chordae tendineae. I: Scanning electron microscopy

Abstract: The formation of the chordae tendineae of the left atrioventricular valve in the chick embryo is described using scanning electron microscopy. These supportive structures for the valve cusps develop between days 6 and 13 of incubation. Elevations which represent the primitive papillary muscles form on the ventricular wall. These elevations bifurcate into thin, web-like folds which are attached to the primitive valve cusps. The folds are the primordia of the chordae tendineae. Linear ridges develop on the web b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
(9 reference statements)
2
11
1
Order By: Relevance
“…Instead, perforations through the closing plates and oral membrane appear to be brought about by cellular rearrangement and disassembly of intercellular junctions resulting in the separation of intact adjacent cells. This may be a characteristic feature of the union between basal epithelial surfaces since similar cellular reorientation has been demonstrated during formation of the foramina secunda in the interatrial septum (Morse and Hendrix, 1980), during development of chordae tendineae (Morse et al, 1984), and during disappearance of the dorsal mesocardium (Litke and Johnson, 1980) in the chick heart.…”
Section: Discussionsupporting
confidence: 53%
“…Instead, perforations through the closing plates and oral membrane appear to be brought about by cellular rearrangement and disassembly of intercellular junctions resulting in the separation of intact adjacent cells. This may be a characteristic feature of the union between basal epithelial surfaces since similar cellular reorientation has been demonstrated during formation of the foramina secunda in the interatrial septum (Morse and Hendrix, 1980), during development of chordae tendineae (Morse et al, 1984), and during disappearance of the dorsal mesocardium (Litke and Johnson, 1980) in the chick heart.…”
Section: Discussionsupporting
confidence: 53%
“…It has been suggested that myocardium transdifferentiates into fibrous tissues during valvar formation, or mesenchymal cells into myocardium during the "muscularization" of the mesenchymal septal structures. 7,13,31 However, the pattern of labeling in the ␣MHC-Cre/R26R embryos was identical to the pattern of expression of Serca2 and complementary to the pattern of labeling in the Tie2-Cre/ R26R embryos. Therefore, we conclude that after the onset of recombination in the heart at E8 to E9, there is no transdifferentiation of either myocardial cells or endocardial cells and their derived mesenchyme.…”
Section: Discussionmentioning
confidence: 68%
“…2,3,7,[11][12][13] Using the recombination system, we have shown for the first time that the myocardial lineage does not contribute materially to the definitive fibrous tissues of the heart, including the valvar leaflets and cords of the tension apparatus. Our data indicate that these components are generated almost entirely from the cells derived from the endocardium, a finding also reported very recently by Lincoln et al, 32 although we cannot rule out the possibility that small numbers of cells of nonendocardial origin are present in these components.…”
Section: Contributions Of Different Tissue To the Valvar Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…Those structures are in direct contact with blood flow and actuate determining the adequate blood course, participating directly in the myocardium contractile function. The structure of left atrioventricular valve apparatus is composed by the mitral annulus, mitral valve leaflets, chordae tendineae and papillary muscles and has been studied elsewhere [15,16] concerning the diseases that attempt its integrity and function, including its morphogenesis [17,18].…”
Section: Introductionmentioning
confidence: 99%